Persalinan Harus Dilakukan di Fasilitas Kesehatan - Nasution, Mutiah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study discusses the implementation of the Regulation of the Minister of Health Number 97 of 2014 Article 14 Paragraph (1) concerning Childbirth Must Be Performed at Health Service Facilities in Batang Gadis Village, Panyabungan Barat District, Mandailing Natal Regency. This research is motivated by the low utilization of health services in pregnancy and childbirth examinations, whether it is health centers or hospitals or existing health service facilities and infrastructure, causing implementation that is not in accordance with existing regulations. This type of research is a field research using a qualitative descriptive analysis method. The method of collecting data in this research is by interview and documentation in accordance with the provisions contained in the Regulation of the Minister of Health Number 97 of 2014 Article 14 Paragraph (1) concerning Childbirth Must Be Done at Health Service Facilities in Batang Gadis Village, West Panyabungan District, Mandailing Regency. Christmas. The parties studied were the Mandailing Natal Health Office, the West Panyabungan Health Center and the community of Batang Gadis village, West Panyabungan District, Mandailing Natal Regency. The results of the study stated that the implementation of the Regulation of the Minister of Health Number 97 of 2014 Article 14 Paragraph (1) concerning Childbirth Must Be Done at Health Service Facilities in Batang Gadis Village, Panyabungan Barat District, Mandailing Natal Regency has not been implemented properly because many people in Batang Gadis Village still give birth. in non-health care facilities and choose to use traditional methods such as using the services of a traditional birth attendant (traditional traditional birth attendant) where delivery is carried out at home.